ACE-Inhibitor Related Angioedema Is Not Sufficiently Reported to the Danish Adverse Drug Reactions Database - Cornwall, Johan Emil Lundbek (Drug Healthc Patient Saf, 2019)
PURPOSE: The primary objective of this study was to calculate the report rate of angiotensin-converting enzyme inhibitor-related angioedema (ACEi-AE). Secondary objectives were to determine factors suspected to affect the likelihood of ACEi-AE being reported and to investigate potential differences in angioedema risks between different ACEis. PATIENTS AND METHODS: Patient data from two cohorts comprising 176 patients with ACEi-AE were compared with report data from the Danish Adverse Drug Reactions Database, administered by the Danish Medicines Agency (DKMA). The study period was 1994–2015. Data were linked using unique personal identification numbers and birth dates. Cohort data and report data were compared with ACEi sales numbers from MedStat, an official database containing annual pharmaceutical drug sale data in Denmark. RESULTS: ACEi-AE was reported in two out of 176 cases resulting in a report rate of 1.1%, meaning that 98.9% of the cases were not reported. Since 1994, a total of 417 ACEi-AE reports were made to the DKMA. Fifty-eight percent of these were made by general practitioners or physicians with unknown workplaces and 35% by hospital staff. Enalapril and ramipril were the most sold ACEi’s in the study period (40.3% and 42.6%, respectively). Enalapril was associated with 54.7% of ACEi-AE reports while ramipril was associated with 14.2%. ACEi substance received was known for 141 cohort patients, of which 53.9% were prescribed enalapril and 17.0% received ramipril. CONCLUSION: ACEi-AE was found to be severely underreported in Denmark, greatly limiting the available incidence data for this potentially life-threatening adverse reaction.